Web application for mobile laboratory information system - Zhang, Haolin (2013)
Laboratory Information System (LIS) is one of the main systems in Hospital Information Systems (HIS). The fast growing technologies on laboratory information system provides easy and instant communication between doctors and laboratory assistants, especially when they have the system on mobile devices. It helps to reduce significant time of carrying paper documents around the hospital for patients. Instant information of patients can be transmitted to laboratories once the doctor makes a test requests. The request can be deleted or modified by doctor if the test is not processed yet. The status of the requests can be monitored by doctor, and modified by lab assistant. The lab assistant can search pending requests by test terms. Once the result is uploaded by lab assistant, including value description of a test as well as image of the test, the doctor can search for it according to test terms and patient ID easily for future examination advices.